2012
DOI: 10.1007/s11284-012-1005-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of GPS location clusters analysis to study predation, feeding, and maternal behavior of the Eurasian lynx

Abstract: Analysis of global positioning system (GPS) location clusters (GLCs) is becoming increasingly popular in studies of carnivore ecology. While promising, this application of GPS technology is still poorly developed for most species. We applied this method to study predation and maternal behavior of the Eurasian lynx (Lynx lynx) in Dinaric Mountains. Low population densities, rugged terrain, dense vegetation, and administrative borders make studies of this endangered population using traditional methods and a lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 32 publications
2
56
0
3
Order By: Relevance
“…The numerous reports of successfully deployed GPS collars in different environmental settings convincingly illustrate the potential that this equipment holds for obtaining large quantities of high quality data in wildlife research (Edenius 1996;Eriksen et al 2011;Martins et al 2011;Harju et al 2013;Krofel et al 2013). However, the use of GPS collars often comes with unforeseen technical or data quality issues (Sager-Fradkin et al 2007;Matthews et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The numerous reports of successfully deployed GPS collars in different environmental settings convincingly illustrate the potential that this equipment holds for obtaining large quantities of high quality data in wildlife research (Edenius 1996;Eriksen et al 2011;Martins et al 2011;Harju et al 2013;Krofel et al 2013). However, the use of GPS collars often comes with unforeseen technical or data quality issues (Sager-Fradkin et al 2007;Matthews et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Svoboda et al (2013) found that clusters with more locations increased their odds of finding a bobcat (Lynx rufus) kill site. Krofel et al (2013) used GPS cluster locations to find kill sites and den sites of Eurasian lynx (Lynx lynx), with 99% of the kill sites found at clusters longer than 30 h and with a minimum of two locations within 300 m. Our research is the first attempt to use spatial, temporal, and habitat characteristics of potential clusters to identify jaguar kill sites in South America. We found that the duration of time a jaguar spent at the cluster, the number of nights a jaguar spent at a cluster and the dispersion of the points at the cluster were the best predictors of whether a cluster was associated with a kill.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GPS collars can provide data on movement distances, which are useful for estimating population density when combined with remote camera trapping (Soisalo and Cavalcanti 2006), as well as information on denning behaviour (e.g. Krofel et al 2013). The only disadvantages of GPS collars may be the initial costs and the bias for large prey when the relocation acquisition schedule of the GPS collars is temporally far enough apart between locations that small prey items are completely consumed in that time interval, and therefore no cluster is identified for investigation in the field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations